Autoimmunity and clinical pathology amelioration in SLE by dexamethasone primed mesenchymal stem cell derived conditioned media - Khushbu Priya; Sonali Rawat; Doli Das; Manaswi Chaubey; Hiral Thacker; Kiran Giri; Shambhavi Singh; Madhukar Rai; Sujata Mohanty; Geeta Rai (Stem Cell Research & Therapy)
Abstract Background This study aimed to investigate the therapeutic potential of cell-free Dexamethasone (Dex) primed Wharton’s jelly Mesenchymal stem cells derived conditioned media (DW) in addressing complications associated with systemic lupus erythematosus (SLE), focusing on its immunomodulatory effects. Methods Peripheral blood mononuclear cells from 74 SLE patients were stimulated and treated with Dex, DW and W. Culture supernatant were evaluated for autoantibody levels, IL-10 and TGF-β by ELISA, Treg subtypes, Breg subtypes, TH17 cells Double negative T cells and inflammatory neutrophils by flow cytometry, IL-10 and IL-17A by qPCR. In vivo studies were performed on 60 pristane induced female BALB/c mice. Dex and DW treatments were evaluated for autoantibody production, proteinuria, immunomodulation of immune cells, organ function, and histopathology. In vivo imaging of internal organs was done using VevoLAZR-X photoacoustic imaging system. Results DW treatment significantly expanded different Treg and Bregs subtypes. DW suppressed pathogenic TH17, Double negative T cells and inflammatory neutrophils. Comparative analyses with hydroxychloroquine showed similar effects, with combined treatment enhancing efficacy. Inhibition studies implicated the TGF-β pathway in DW's mechanism. In vivo studies using the PIL mouse model showed that DW treatment reduced mortality, prevented proteinuria, and ameliorated symptoms such as limb inflammation, seizures, and alopecia. Detailed organ-specific evaluations through live imaging and histopathological analyses revealed DW’s protective effects on kidneys, liver, lungs, heart, and spleen. Conclusion DW shows promise as a cell-free biological therapy for SLE and related autoimmune disorders, capable of modulating immune responses effectively without the adverse effects of glucocorticoids.